Transformation of Educational Management in the Era of Online Media: An Analysis of Digital Corporate Responsibility - Bambang Suyanto; Abdul Basit; Slamet Pamuji (JUMPA : Jurnal Manajemen Pendidikan, 2025)
This study examines the transformation of educational management in the era of online media, with a focus on the role and responsibility of digital corporations in shaping information ecosystems. The rapid expansion of digital platforms has fundamentally altered how knowledge is produced, accessed, and managed, placing educational institutions within complex and interconnected information environments. However, the dominance of digital corporations as information gatekeepers raises critical challenges related to accountability, misinformation, and the quality of educational content. This research employs a Systematic Literature Review (SLR) approach by analyzing peer-reviewed articles published between 2020 and 2025 from databases such as Scopus, ScienceDirect, and Google Scholar. The review process follows PRISMA guidelines, including identification, screening, eligibility, and inclusion stages. Data were analyzed using thematic analysis to identify key patterns related to digital transformation, information governance, and corporate accountability. The findings reveal that educational management has shifted toward a networked digital system where online media plays a central role in knowledge acquisition. Digital corporations significantly influence information visibility through algorithmic systems, yet their accountability remains limited, particularly in addressing misinformation. In addition, weak regulatory frameworks and limited multi-stakeholder collaboration further complicate efforts to ensure information quality. The study concludes that educational management must adopt adaptive and responsive strategies by integrating digital literacy, critical thinking, and information governance. Strengthening collaboration between educational institutions, policymakers, and digital corporations is essential to create a more accountable and sustainable digital education ecosystem.